Integrated single-cell and spatial transcriptomics reveal the differentiation drivers of gastric epithelial lineage progression - Chen, Xuyu; Jiang, Xin; Wang, Siying; Xia, Jianlei; Wang, Wenjun; Fu, Xinyu; Yukun, Ping; Liu, Zhuoqi; Li, Yaoyao; Zhang, Min; Ding, Yanbing (Frontiers in Immunology, 2026)
Gastric cancer (GC) develops through a sequence from chronic gastritis to intestinal metaplasia (IM) and carcinoma, with Helicobacter pylori (HP) as a key driver; however, the molecular mediators linking inflammation to malignant transformation remain unclear. We integrated single-cell RNA sequencing and spatial transcriptomics of gastric mucosal samples from atrophic gastritis, IM, and GC, including HP positive (+) and HP negative (-) cases, to map cellular heterogeneity, differentiation trajectories, and pathway activities. Our analyses revealed that IM epithelium represents a transitional state between normal and malignant epithelial lineages, characterized by enhanced WNT signaling that promotes neoplastic progression, whereas H. pylori–associated inflammation activates NF-κB signaling. Across analysis, UPP1 was consistently upregulated in malignant and H. pylori–positive epithelium, increasing along pseudotime toward cancer-like states. Spatial mapping and organoid experiments confirmed that UPP1-high cells had higher intestinal differentiation scores, while UPP1 knockout promoted IM-like morphology in WNT-depleted cultures. Clinically, UPP1 was elevated in GC versus normal tissues, correlated with advanced TNM stage, predicted poor survival, and was higher in HP+ tissues. Knockdown in GC cell lines reduced clonogenicity and migration. Collectively, these findings identify UPP1 as a key regulator of epithelial reprogramming and IM, linking H. pylori–driven inflammation with WNT-mediated differentiation, and highlight its potential as a prognostic biomarker and therapeutic target in GC.